2017
DOI: 10.3340/jkns.2017.0101.013
|View full text |Cite
|
Sign up to set email alerts
|

Multiloculated Hydrocephalus : Open Craniotomy or Endoscopy?

Abstract: Multiloculated hydrocephalus (MLH) is a condition in which patients have multiple, separate abnormal cerebrospinal fluid collections with no communication between them. Despite technical advancements in pediatric neurosurgery, neurological outcomes are poor in these patients and the approach to this pathology remains problematic especially given individual anatomic complexity and cerebrospinal fluid (CSF) hydrodynamics. A uniform surgical strategy has not yet been developed. Current treatment options for MLH a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
25
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 26 publications
1
25
0
Order By: Relevance
“…Therefore, this strategy for complicated hydrocephalus was reliable. The incurrence of infection as a result of the shunt implantation in the literature varies widely from 0.17% to 13.2% [4]. Consistent with previous reports, the rate of infection in our study was 3.6%.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Therefore, this strategy for complicated hydrocephalus was reliable. The incurrence of infection as a result of the shunt implantation in the literature varies widely from 0.17% to 13.2% [4]. Consistent with previous reports, the rate of infection in our study was 3.6%.…”
Section: Discussionsupporting
confidence: 91%
“…The existing evidence at case series level seems to favor neuro-endoscopy as the rst line of treatments over traditional shunt surgery [3]. However, VPS is still the treatment of choice in communicating hydrocephalus or in patients after the failure of endoscopic fenestration [4]. Besides, the decision on what treatment to apply should be based on individual anatomy, underlying pathology, available techniques, and the experience of the treating surgeon [5].…”
Section: Discussionmentioning
confidence: 99%
“…Both microsurgical and endoscopic septal fenestration techniques have been described to serve the aforementioned surgical goals. [ 1 , 8 , 18 , 27 , 29 , 30 ] They can communicate the cysts to be eventually drained by a single shunt catheter. Little published data exist that assess both surgical approaches in details.…”
Section: Introductionmentioning
confidence: 99%
“…A study done by Jung Won Choi et al reviewed the surgical outcomes of intracranial arachnoid cysts and concluded that fenestration of cysts is associated with more surgical complications [ 11 ]. However, some studies suggest that neuroendoscopy remains a superior approach, with a lower risk of surgical complications associated with craniotomy and shunting [ 12 - 13 ]. In a case series on the endoscopic approach, a success rate of up to 71–81% has been documented [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, some studies suggest that neuroendoscopy remains a superior approach, with a lower risk of surgical complications associated with craniotomy and shunting [ 12 - 13 ]. In a case series on the endoscopic approach, a success rate of up to 71–81% has been documented [ 12 ]. Furthermore, with associated hydrocephalus, the possibility of larger spaces makes this treatment option easier to execute.…”
Section: Introductionmentioning
confidence: 99%